Pengaruh Penerapan Agroforestry Kopi Dengan Tanaman Buah-Buahan, Cabai Dan Ternak Terhadap Peningkatan Pendapatan Petani Di AtuLintang, Kabupaten Aceh Tengah - Rifatul Huhasna; Mustafa Usman; T Fauzi (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
This study aims to Know the adoption of agroforestry coffee with fruit crops, chili and livestock can increase the income of farmers in the district Atu Lintang, Aceh Tengah . Sampling in this study was carried out using Proportional Stratified Random Sampling, namely the selection of stratified random samples from the entire existing population where each strata was represented by a sample whose number was determined proportionally. Strata in this case is the pattern of farming carried out. The total sample on this research ar 24 farmers. The analytical techniques used in this study are income analysis and business feasibility and t test (Independent sample T Test). The results showed that thesystem agroforestry coffee with fruit, chili and livestock plants in Atu Lintang District, Aceh Tengah Regency provided a higher income or profit Rp. 89,598,278/Ha, while thesystem of agroforestry coffeein Atu Lintang District, Aceh Tengah Regency provides an income or profit of Rp 19,824,772/ha. The results of the t-test test also explain that in the system of coffee agroforestry and agroforestry coffee with fruit crops, chilies and livestock there are significant differences, where the income in the system agroforestry coffee with fruit crops, chili and livestock is greater than the income in the agroforestry coffee system Ha/year.